Identification of main human urinary metabolites of the designer nitrobenzodiazepines clonazolam, meclonazepam, and nifoxipam by nano-liquid chromatography-high-resolution mass spectrometry for drug testing purposes - Meyer, Markus Robert (Analytical and bioanalytical chemistry, 2016)
Among the new psychoactive substances (NPS), so-called designer benzodiazepines have become of particular importance over the last 2 years, due to their increasing availability on the internet drug market. Therapeutically used nitrobenzodiazepines such as flunitrazepam are known to be extensively metabolized via N-dealkylation to active metabolites and via nitro reduction to the 7-amino compounds. The aim of the present work was to tentatively identify phase I and II metabolites of the latest members of this class appearing on the NPS market, clonazolam, meclonazepam, and nifoxipam, in human urine samples. Nano-liquid chromatography-high-resolution mass spectrometry was used to provide data about their detectability in urine. Data revealed that clonazolam and meclonazepam were extensively metabolized and mainly excreted as their amino and acetamino metabolites. Nifoxipam was also extensively metabolized, but instead mainly excreted as the acetamino metabolite and a glucuronic acid conjugate of the parent. Based on analysis of human urine samples collected in cases of acute intoxication within the Swedish STRIDA project, and samples submitted for routine drug testing, the most abundant metabolites and good targets for urine drug testing were 7-aminoclonazolam for clonazolam, 7-acetaminomeclonazepam for meclonazepam, and 7-acetaminonifoxipam for nifoxipam.
Gesehen am 18.10.2019